Dissociation of potentiation of isoprenaline by cocaine from inhibition of uptake in cat spleen - Davidson, W. J. (1970)
1. Cocaine hydrochloride, 10 μg/ml, potentiated isoprenaline and noradrenaline in isolated spleen strips from normal cats and from cats treated with reserpine 24 h previously. 2. Isoprenaline was taken up almost as well as noradrenaline by spleen strips from cats treated with reserpine. 3. Cocaine blocked uptake of noradrenaline but did not reduce uptake of isoprenaline. Drug concentrations used in these studies were the same as in potentiation experiments. 4. It is concluded that inhibition of uptake is not the mechanism by which cocaine potentiates the effect of isoprenaline on the spleen and might be only a contributory factor in the case of noradrenaline potentiation.